(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
Vocabulary perception is always in the focus of scientists. The article discusses the functioning odorativnoy vocabulary in the works of I. Nechui-Levitsky defined word-forming nest with certain roots and relevant thematic groups of tokens with the semantics of «smell».